PENGARUH SUBSTITUSI SILASE ISI RUMEN SAPI PADA PAKAN BASAL RUMPUT DAN KONSENTRAT TERHADAP KINERJA SAPI POTONG - , ENGKUS AINUL YAKIN, S.Pt, Prof. Dr. Ir. Nono Ngadiyono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study aims to determine the effect of substitution of rumen contents silage on the performance of beef cattle. As many as 12 heads of cattle aged 1.5 to 2 years used in this study for 8 weeks (2 months) with feeding of 3% of body weight based on dry matter and given drinking water ad libitum. Treatment to be given to grass was by replacing some grass with rumen contents silage. The treatment were, TO was 100% grass, T1 was 25% silage of rumen contents and 75% grass, and T2 was 50% silage of rumen contents and 50% grass. Balance between grass and concentrate was 20% : 80%. Variable observed was feed consumption, feed digestibility, average daily gain (ADG), feed conversion, and feed cost per gain. The results showed that treatment were significantly different (P<0.05) on CP, CF consumption and DM, CF digestibility, while the treatment were not significantly different on DM, OM, TDN consumption, average daily gain (T0 = 0.92 ± 0.02, T1 = 0.97 ± 0.05, and T2 = 0.96 ± 0.03 kg/head/day), feed conversion (T0 = 14.30 ± 0.69, T1 = 14.16 ± 1.46, and T2 =13.45 ± 0.70), OM, CP digestibility and feed cost per gain. It was concluded that the substitution of grass with silage of rumen contents until 50% were different but not significantly on average daily gain, feed conversion, and feed cost per gain